A New MEN2 Syndrome with Clinical Features of Both MEN2A and MEN2B Associated with a New RET Germline Deletion. (29th July 2020) - Giani, Carlotta; Ramone, Teresa; Romei, Cristina; Ciampi, Raffaele; Tacito, Alessia; Valerio, Laura; Agate, Laura; Ugolini, Clara; Marinò, Michele; Basolo, Fulvio; Franchi, Alessandro; Borsari, Simona; et al.
Abstract : Background . Multiple endocrine neoplasia type 2 (MEN2) is a hereditary cancer syndrome caused by RET proto-oncogene mutation. Two different clinical variants of MEN2 are known (MEN2A and MEN2B): medullary thyroid carcinoma (MTC) almost always present and associated with pheochromocytoma (Pheo), and primary hyperparathyroidism (HPTH) in MEN2A and with Pheo and other nonendocrine diseases in MEN2B. Case Report . A 7-year-old girl, previously treated for a pelvic plexiform neurofibroma, arrived at our observation with a peculiar MEN2B syndrome and with HPTH. The neck ultrasound showed bilateral thyroid nodules, local lymph node lesions, and a suspicious left hyperplastic parathyroid. The CT scan showed a megacolon and described the persistence of the pelvic tumor. A new RET germline deletion in exon 11 (c.1892_1899delCGAGCT; p.Glu632_Leu633del) was found. She underwent total thyroidectomy, central compartment and latero-cervical lymph node dissection, and neck exploration for primary HPTH. The histology confirmed bilateral MTC, multiple lymph node metastases, a hyperplastic parathyroid, and a parathyroid adenoma. Conclusions . This is the first case of a complex syndrome characterized by peculiar features of MEN2B, without Pheo but with a pelvic plexiform neurofibroma and with HPTH, which is typical of MEN2A. A "de novo" new germline RET deletion located in exon 11 was found.